Strategies to Increase Professional Zakat Awareness among Civil Servants in West Java - Supriandi (Westscience Press, 2024)
This study explores strategies to enhance professional zakat awareness among civil servants in West Java through a quantitative analysis involving 150 participants. Employing SPSS version 25 for data analysis, the research identifies key factors influencing zakat awareness, including socio-economic background, religious education, and the effectiveness of zakat campaigns. The findings highlight significant correlations between these factors and zakat awareness, suggesting that tailored educational programs and targeted communication strategies can effectively improve awareness and compliance. The study provides valuable insights for policymakers and religious organizations aiming to boost zakat contributions among civil servants, ultimately supporting socio-economic development in West Java.